Survey Responses of School Closures During the COVID-19 Outbreak in Taiwan - Chao, Kuo-Yu; Hsiao, Tung-Yuan; Cheng, Wei (Frontiers in Public Health, 2022)
Background: Taiwan faced a surge in new COVID-19 infections in May 2021. Because the new cases increased quickly, parents called for school closures. A national parent group used an online survey to collect parents’ opinions of school closures from May 17 to 18, 2021. Methods: An online survey titled “Survey of Opinions of School Closures During the Current COVID-19 Outbreak” (SOSC-COVID-19) was designed and sent to local parent groups, which then sent it to parents throughout Taiwan from May 17 to 18, 2021, in Taiwan. Results: A total of 8,703 completed surveys were analyzed. All parents wanted schools to close, and chi-square analyses showed no significant differences between participants inside and outside municipalities or participants from areas with economic scores above or below 40. Qualitative feedback indicated that parents were concerned about students’ health, economic considerations, and whether governments or parents should decide to suspend classes. After the survey, school closures were announced in the afternoon of May 18. The number of new COVID-19 cases among students once flared up but then decreased 1 month later after school closures. Conclusions: Although school closures have impacted on all families, low-income families were affected the most. Families in the areas with economic score under 40 or elsewhere all responded rather similarly. Despite the fact that nationwide school closures cannot totally stop transmission within the families, school closures can potentially hinder transmission between students during COVID-19 outbreak.